Calidad fisicoquímica del producto terminado Dexametasona 0,5 mg/5 mL solución oral de un Laboratorio Farmacéutico Nacional- Trujillo 2019 - Guevara de la Cruz, Katherine Milagro (2019)
His report of pre-professional practices aims to determine the physicochemical quality of the finished product Dexamethasone 0.5mg / 5mL oral solution of a national pharmaceutical laboratory-Trujillo 2019. For which the sample consisted of 60 units of the product Dexamethasone 0, 5g / 5mL oral solution obtained from random sampling according to the finished product sampling procedure. For its methodology it was based on the development of the analytical technique based on the monograph of USP 40, which were: Description, pH, specific gravity, identification, assessment. The results obtained were: Description of the sample: Slightly sirupous solution, red in color, with aromatic odor and particular flavor; Delivery volume: 102 ml, the pH was 3.43 (23-25 ° C), the specific gravity was 1,117; the identification of the sample by thin layer chromatography complies with the values and in the HPLC identification it complies with the retention times corresponding to Dexamethasone according to the titration test; and in the titration test: 0.518 mg / 5ml of Dexamethasone (103.6%). Concluding that the finished product Dexamethasone 0.5mg / 5mL oral solution of a national pharmaceutical laboratory complies with the specifications in the physicochemical quality tests according to the American Pharmacopeia monograph (USP40-NF35).